Academic origins and characteristics of the Chinese stylistic restoration - Xi Chen (Frontiers of Architectural Research, 2016)
The conservation practice in China, termed “Chinese stylistic restoration” in this study, has been influenced by the traditional Chinese philosophy and construction principles, the modern Chinese conservation theory of Liang Sicheng and Liu Dunzhen, and Western and international theories and policies concerning conservation. This study uses three case studies, namely, Shanghai Zhenru Temple, Jianfu Palace Garden, and Angkor Wat Chau Say Tevoda Temple, to demonstrate the main characteristics of the Chinese stylistic restoration, including its emphasis on style over authenticity, pursuit of a gestalt form, and flexible attitude toward reconstruction. Accordingly, these practices have shaped the current Chinese conservation theory as reflected in the case studies reported in “Principles for the Conservation of Heritage Sites in China” and the Qufu Declaration.